IMAGINE : un ensemble de méthodes et d'outils pour contribuer à la gestion intégrée des zones côtières en Méditerranée - Élisabeth Coudert; Mohamed Larid (VertigO)
In order to meet the needs of the sustainable coastal zone management in the Mediterranean, Blue Plan jointly with Dr Simon Bell (Bayswater Institute, UK) has developed the Imagine approach which allows to build a sustainable development vision and an area project by mobilizing actors within a participatory process, to describe, assess and examine the level of sustainability of a local system in the past, present and future by means of indicators and to set goals to be achieved and to follow progress of the system towards sustainable development.It is based on systemic analysis, indicators and the sustainability threshold concept, prospective. It is a dynamic and participatory process using local actors' expertise. The above items are first described. Then the implementation is explained according to an Imagine exercise in Algeria (2003-2004). The conclusion summarizes difficulties and contributions of the method within an integrated coastal area management project.systemic, prospective, sustainability, indicators, participation, coastal area, Algeria, Mediterranean.